Standardizing Malaysian vehicle registration number plate / M. R. Ruzali and G. Daimin - Ruzali, M. R.; Daimin, G. (2016)
Every registered vehicle posses it's own unique registration number as identity recognition. It is like a citizen owning his or her own identification number in identification card, MyKad for example in Malaysia. This unique vehicle registration number regularly being used as first reference in obtaining information regarding the vehicle. Internationally, it is necessity to display registration number at each front and backside of every vehicles. Application of number plate display format is vary in different countries. Again, the presentation of vehicle registration number plate is persistence as a national vehicle passport. As citizen of a nation, passport is the citizen's pride when travelling and so does the exhibition of Malaysian vehicle number plate. Malaysian vehicle registration number plate was adapted from Britain's car registration number plates that were brought in by the governors from Britain. It was before the establishment of Lembaga Pengangkutan Jalan on 1937. Later on 1st April 1946, Lembaga Pengangkutan Jalan was converted to Jabatan Pengangkutan Jalanraya (JPJ) under Kementerian Pengangkutan dan Jalan. Since establishment, Malaysian vehicle number plate had encountered very few updates in visuals and formats. The outcome of this study will be proposed to Jabatan Pengangkutan Jalanraya Malaysia to overcome the substandard Malaysian vehicle license number plate.